If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (4n + -3)(2n + 1) = 0 Reorder the terms: (-3 + 4n)(2n + 1) = 0 Reorder the terms: (-3 + 4n)(1 + 2n) = 0 Multiply (-3 + 4n) * (1 + 2n) (-3(1 + 2n) + 4n * (1 + 2n)) = 0 ((1 * -3 + 2n * -3) + 4n * (1 + 2n)) = 0 ((-3 + -6n) + 4n * (1 + 2n)) = 0 (-3 + -6n + (1 * 4n + 2n * 4n)) = 0 (-3 + -6n + (4n + 8n2)) = 0 Combine like terms: -6n + 4n = -2n (-3 + -2n + 8n2) = 0 Solving -3 + -2n + 8n2 = 0 Solving for variable 'n'. Factor a trinomial. (-1 + -2n)(3 + -4n) = 0Subproblem 1
Set the factor '(-1 + -2n)' equal to zero and attempt to solve: Simplifying -1 + -2n = 0 Solving -1 + -2n = 0 Move all terms containing n to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + -2n = 0 + 1 Combine like terms: -1 + 1 = 0 0 + -2n = 0 + 1 -2n = 0 + 1 Combine like terms: 0 + 1 = 1 -2n = 1 Divide each side by '-2'. n = -0.5 Simplifying n = -0.5Subproblem 2
Set the factor '(3 + -4n)' equal to zero and attempt to solve: Simplifying 3 + -4n = 0 Solving 3 + -4n = 0 Move all terms containing n to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -4n = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -4n = 0 + -3 -4n = 0 + -3 Combine like terms: 0 + -3 = -3 -4n = -3 Divide each side by '-4'. n = 0.75 Simplifying n = 0.75Solution
n = {-0.5, 0.75}
| -3m-6(6+3m)=-141 | | a-1=5a+3p-8 | | 9-3(4x-7)=5x+37 | | -5(16.5+3t)=3(9-t) | | 37-7r=4-8(1+7r) | | -3(2x+6)+6(6x+5)=42 | | -2=v+2-5v | | 39x+132-31=38243 | | 4x+2=1x+4 | | (-4)*(-4)*(-4)*(1)= | | 32=w | | 5+16x=-59 | | 16=10m-14 | | 2+4(x+2)=7(x+1)-9 | | 5(6x+2)+4(1-4x)=14 | | 4x^5-4x= | | 45.49=n/2+5 | | 8v-4(v-8)=8 | | 14x-9x-11+17=-3x+78 | | 6(3a+1)-30=8(2a-4) | | 2x-2=3X+8 | | 39x+4(1413-981)=187367 | | -28=-2(n+5)-(-6n+6) | | 5Z=1.50 | | 0.80x+.05(2-x)=.10(76) | | 3(x-2y)= | | 6/8=x | | 5XZ=1.50 | | 3x-(11)=34+2x | | -2-(3-5t)= | | 8x=4(7x+25) | | 2=2(k+3)+4(5-2k) |